The Relationship Between Principal Leadership and Teacher Performance in Islamic Boarding Schools; Meta-Analysis - Khairunnisa; Zohriah, Anis; Iriyadi, Deni (PT FORMOSA CENDEKIA GLOBAL, 2024)
The aim of this research is to be able to see general (comprehensive) conclusions about the relationship between school principal leadership and teacher performance. The approach used was Meta-Analysis and systematic review using JASP 0.18.1.0 software. The data found were 20 articles through searches on Google Scholar and Mendeley search with the keywords principal leadership, teacher performance and Islamic boarding schools, and 11 articles were selected based on predetermined characteristics. Data taken from selected articles are the number of samples (N) and the r value from each article, then the effect size is analyzed. This research aims to analyze the correlation or relationship between school principal leadership and teacher performance in Islamic boarding schools. Data from research on principal leadership on teacher performance in Islamic boarding schools were analyzed in depth to find the strength of the correlation between principal leadership and teacher performance in Islamic boarding schools. This research started by formulating a research topic, exploring relevant research results for analysis. The research results show that the principal's leadership is able to improve teacher performance in Islamic boarding schools. The results of analysis using the random effect model show that there is a significant positive correlation between school principal leadership and teacher performance.